Occupation and risk of non-hodgkin lymphoma and its subtypes: A pooled analysis from the interlymph consortium - Mannetje, A.; De Roos, A.; Boffetta, P.; Vermeulen, R.; Benke, G.; Fritschi, Lin; Brennan, P.; Foretova, L.; Maynadié, M.; Becker, N.; Nieters, A.; Staines, A.; et al. (US Department of health Human Sciences National INST of Health Science, 2016)
Background: Various occupations have been associated with an elevated risk of non-Hodgkin lymphoma (NHL), but results have been inconsistent across studies. Objectives: We investigated occupational risk of NHL and of four common NHL subtypes with particular focus on occupations of a priori interest. Methods: We conducted a pooled analysis of 10,046 cases and 12,025 controls from 10 NHL studies participating in the InterLymph Consortium. We harmonized the occupational coding using the 1968 International Standard Classification of Occupations (ISCO-1968) and grouped occupations previously associated with NHL into 25 a priori groups. Odds ratios (ORs) adjusted for center, age, and sex were determined for NHL overall and for the following four subtypes: diffuse large B-cell lymphoma (DLBCL), follicular lymphoma (FL), chronic lymphocytic leukemia/ small lymphocytic lymphoma (CLL/SLL), and peripheral T-cell lymphoma (PTCL). Results: We confirmed previously reported positive associations between NHL and farming occupations [field crop/vegetable farm workers OR = 1.26; 95% confidence interval (CI): 1.05, 1.51; general farm workers OR = 1.19; 95% CI: 1.03, 1.37]; we also confirmed associations of NHL with specific occupations such as women’s hairdressers (OR = 1.34; 95% CI: 1.02, 1.74), charworkers/cleaners (OR = 1.17; 95% CI: 1.01, 1.36), spray-painters (OR = 2.07; 95% CI: 1.30, 3.29), electrical wiremen (OR = 1.24; 95% CI: 1.00, 1.54), and carpenters (OR = 1.42; 95% CI: 1.04, 1.93). We observed subtype-specific associations for DLBCL and CLL/SLL in women’s hairdressers and for DLBCL and PTCL in textile workers. Conclusions: Our pooled analysis of 10 international studies adds to evidence suggesting that farming, hairdressing, and textile industry–related exposures may contribute to NHL risk. Associations with women’s hairdresser and textile occupations may be specific for certain NHL subtypes.